Critical Damage and Microstructure Characteristics of Sandstone in the Three Gorges Reservoir Area by Single Specimen Method Under Different Stress Paths - Li, Hua; Wang, ZhiPeng; Dai, Lingquan; Wan, Liangpeng; Deng, Huafeng; Yang, Chao; Chen, Jianghong; Pan, Hongyue; Wang, Lei; Jiang, Qiao (Frontiers in Physics, 2022)
The critical damage value of rock is an important parameter of stability analysis when engineering rock mass. Based on the previous single test method, this paper, combined with the deformation characteristics of rock residual phase under different stress paths, proposed a single specimen repeated loading method to measure the critical damage value of rock based on different damage variables. The paper also proposed to modify the critical damage value based on residual constitutive energy and to improve the definition of damage variables based on constitutive energy dissipation. According to the microstructure characteristics of the rock sample, the mechanism of the single specimen method to determine the critical value of rock sample damage is revealed. The results show that: 1) Comparing the results of triaxial failure test of rock under different stress paths and single specimen repeated loading test, the residual strength of rock sample is mainly controlled by the confining pressure of loading, which is not an obvious relationship with initial confining pressure and stress path; 2) The number of repeated compressions has little effect on the internal structure, particle flatness, and particle surface smoothness of their specimens, which is reflected at the macroscopic level that the residual strength of sandstone tends to achieve a stable value; and 3) The corrected critical damage value based on residual strain energy is closer to the theoretical value. Test methods in this paper can provide useful references for determination of critical damage value.